Tinjauan Hukum Terhadap Tindak Pidana Korupsi Pengadaan Barang dan Jasa Pemerintah - Meiva Mawikere; Adensi Timomor; Joupy G.Z Mambu (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze and understand the problem of corruption in government procurement of goods and services in Indonesia. Corruption in this sector has become a serious issue, considering its detrimental impact on state finances and the people's economy. The research method used is normative juridical, with a statutory approach that refers to applicable regulations. The results of the study indicate that the factors that influence corruption include weak planning and budgeting processes, lack of transparency and accountability, and inadequate law enforcement. In addition, overlapping authorities and high procurement costs also contribute to corrupt practices. This study concludes that to overcome the problem of corruption in government procurement of goods and services, a comprehensive reform of the procurement system is needed, including increasing transparency, accountability, and public participation. In addition, strengthening law enforcement and implementing stricter sanctions against perpetrators of corruption are very important to create a conducive climate for clean and efficient procurement. The recommendations resulting from this study are expected to be a reference for policy makers in creating a procurement system that is more transparent, accountable, and free from corruption, collusion, and nepotism (KKN).